Pengelolaan Limbah Plastik Ramah Lingkungan: Mengedukasi Siswa SMA Jaya Kota Langsa - Erniwiriani; Puspita , Esti Alemia; Maknuni, Jauharil (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Reducing plastic waste is an urgent environmental issue and efforts are needed to educate high school students about environmentally friendly waste management. This study aims to design an effective method of activity to educate SMA Jaya students in Langsa City about the importance of reducing plastic waste. The proposed method of activity includes counseling and presentations, group discussions, field visits. Counseling and presentations will provide students with an initial understanding of plastic waste and its impact on the environment. Group discussions will provide opportunities for students to share knowledge and ideas about reducing plastic waste. Field visits will provide hands-on experience of the waste processing process. The environmental awareness campaign will involve students in disseminating information about reducing plastic waste in schools and surrounding communities. Collaboration with external parties will provide broader insights about reducing plastic waste. The use of eco-friendly alternatives will encourage students to adopt lifestyle changes that reduce the use of single-use plastics. It is hoped that the implementation of this activity method will help Jaya Jaya High School students in Langsa City understand the importance of reducing plastic waste and have practical skills in environmentally friendly waste management. Through collaboration with external parties and involving the community, it is hoped that this effort to reduce plastic waste can achieve a wider and more sustainable impact.